EFFICACY OF PREOPERATIVE SINGLE DOSE ANTIBIOTIC IN PATIENTS UNDERGOING MESH REPAIR FOR INGUINAL HERNIA - Ullah, Bakhtiar; Khan, Shahbaz Ali; Ahmed, Sarfraz; Pasha, Tousif (Journal of Ayub Medical College Abbottabad, 2013)
Background: Inguinal hernia is the commonest type of external hernias. Lichtenstein mesh repair is the most favoured technique of inguinal hernia repair nowadays. It is tension free repair of weakened inguinal wall using polypropylene mesh. The present study was conducted to determine the efficacy of single dose antibiotic with placebo on patients undergoing inguinal hernia mesh repair. Methods: This randomised controlled trial was carried out in the Department of General Surgery, Ayub Teaching Hospital, Abbottabad from January to December 2011. The study population included male patients presenting with primary unilateral inguinal hernia, above 18 years of age. Mesh repair was performed in all patients. The patients were randomly divided into two groups. Patients in group A were given a single dose of antibiotic before inguinal hernia mesh repair and patients in group B were given placebo before inguinal hernia mesh repair. Efficacy of antibiotic and placebo was accessed in terms of surgical site infections (SSIs). Results: A total of 166 cases of inguinal hernia mesh repair patients were recorded during the study period. A total of 83 patients were recruited in each group. Surgical site infection was found in 6 (7.2%) in Group B it was 15 (18.1%). The difference being statistically significant (p=0.036). Conclusion: Antibiotic prophylaxis is a preferred option for mesh plasty. Keywords: Inguinal hernia, Mesh repair, Antibiotics, Infection